Biological insights into the role of TET2 in T cell lymphomas - Carty, Shannon A. (Frontiers in Oncology, 2023)
Peripheral T cell lymphomas (PTCL) are a heterogenous group of mature T cell lymphomas with an overall poor prognosis. Understanding the molecular heterogeneity in PTCL subtypes may lead to improved understanding of the underlying biological mechanisms driving these diseases.Mutations in the epigenetic regulator TET2 are among the most frequent mutations identified in PTCL, with the highest frequency in angioimmunoblastic T cell lymphomas and other nodal T follicular helper (TFH) lymphomas. This review dissects the role of TET2 in nodal TFH cell lymphomas with a focus on emerging biological insights into the molecular mechanism promoting lymphomagenesis and the potential for epigenetic therapies to improve clinical outcomes.